An Integrative Way for Studying Neural Basis of Basic Emotions With fMRI - Gu, Simeng; Wang, Fushun; Cao, Caiyun; Wu, Erxi; Tang, Yi-Yuan; Huang, Jason H. (Frontiers in Neuroscience, 2019)
A central, unresolved problem in affective neuroscience is to understand how emotions are represented in activities of the nervous system. Many studies are striving to find the localization of basic emotions in the brain but failed. Thus many psychologists suspect the specific neural loci for basic emotions, instead, some proposed that there are specific neural structures for the core affects, such as arousal and hedonic value. The reason for this widespread difference might be that basic emotions used previously can be further divided into more “basic” emotions. Here we review brain imaging data and neuropsychological data, and try to address this question with an integrative model. In this model, we argue that basic emotions are not contrary to the dimensional studies of emotions (core affects). We propose that basic emotion should locate on the axis in the dimensions of emotion, and only represent one typical core affect (arousal or valence). Therefore, we propose four basic emotions: joy-on positive axis of hedonic dimension, sadness-on negative axis of hedonic dimension, fear and anger are twin emotions and locate on the top of vertical dimensions. This new model about basic emotions and construction model of emotions is promising to improve and reformulate neurobiological models of basic emotions.